Obesity and cancer: At the crossroads of cellular metabolism and proliferation - O’Rourke, Robert W. (Surg Obes Relat Dis, 2014)
Obesity is associated with an increased risk of cancer. The mechanisms underlying this association include but are not limited to increased systemic inflammation, an anabolic hormonal milieu, and adipocyte-cancer crosstalk, aberrant stimuli that conspire to promote neoplastic transformation. Cellular proliferation is uncoupled from nutrient availability in malignant cells, promoting tumor progression. Elucidation of the mechanisms underlying the obesity-cancer connection will lead to the development of novel metabolism-based agents for cancer prevention and treatment.